2004
DOI: 10.1002/ajh.20108
|View full text |Cite
|
Sign up to set email alerts
|

Association of functional thrombin‐activatable fibrinolysis inhibitor (TAFI) with conventional cardiovascular risk factors and its correlation with other hemostatic factors in a Spanish population

Abstract: Our aim was to determine the associations of functional thrombin-activatable fibrinolysis inhibitor (TAFI) levels in plasma with conventional cardiovascular risk factors, sex and age, and possible correlations with other hemostatic factors in a Spanish population. We included 303 individuals from a Spanish population. Hemostatic factors such as von Willebrand Factor, VII ag, VIIIc, XIc, XIIc, APCR, protein S, protein C, antithrombin, fibrinogen, and t-PA antigen were assayed. The functional TAFI assay was base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1
2

Year Published

2005
2005
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 16 publications
0
4
1
2
Order By: Relevance
“…This combination of lipid parameters suggests that patients with PCOS may have increased atherogenic potential (29). Some studies reported that thrombin-activatable fibrinolysis inhibitor levels correlated with total cholesterol and women with hypercholesterolemia had higher levels of thrombin-activatable fibrinolysis inhibitor (30,31). Conversely, we were not able to show any correlation between thrombin-activatable fibrinolysis inhibitor and lipid parameters, as previously reported (7,22).…”
Section: Discussioncontrasting
confidence: 80%
“…This combination of lipid parameters suggests that patients with PCOS may have increased atherogenic potential (29). Some studies reported that thrombin-activatable fibrinolysis inhibitor levels correlated with total cholesterol and women with hypercholesterolemia had higher levels of thrombin-activatable fibrinolysis inhibitor (30,31). Conversely, we were not able to show any correlation between thrombin-activatable fibrinolysis inhibitor and lipid parameters, as previously reported (7,22).…”
Section: Discussioncontrasting
confidence: 80%
“…There have been previous studies showing increased [2931] or decreased TAFI levels [32, 33] in CAD patients. There have been, however, few reports evaluating the effect of TAFI on clot lysis time in diabetic subjects that demonstrated no effect [34] or hypofibrinolysis [35].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the mouse is unlikely to be a useful comparative model for CPB2 gene expression in inflammatory states. Data from clinical studies in humans have shown positive associations between plasma TAFI concentrations and inflammatory markers such as fibrinogen and C-reactive protein [42,45], although other studies have failed to detect such associations [46][47][48]. One study found markedly elevated plasma TAFI concentrations in a group of patients with assorted inflammatory disorders (Behcet's disease, celiac disease, and Reiter's syndrome) [49].…”
Section: Non-genetic Influences On Plasma Tafi Concentrationsmentioning
confidence: 97%